Renormalized solutions of elliptic equations with variable exponents and general measure data. (December 2020) - Kozhevnikova, L. M.
Abstract: A class of second-order elliptic equations with variable nonlinearity exponents and the right-hand side in the form of the general Radon measure with finite total variation is considered. The existence of a renormalized solution of the Dirichlet problem is proved as a consequence of stability with respect to the convergence of the right-hand side of the equation. Bibliography: 37 titles.